Trade Integration in the East African Community : An Assessment for Kenya - McIntyre, Meredith (IMF Working Papers; Working Paper, 2005)
The paper analyses the potential trade impact of the forthcoming East African Community (EAC) customs union. It examines the trade linkages among the member countries of the EAC and the extent to which the introduction of the EAC common external tariff will liberalize their trade regimes. To gauge the potential trade impact of the formation of the customs union, simulations are conducted for Kenya. The empirical results indicate that the customs union will have a beneficial effect on Kenya's trade. The paper does not draw any conclusions on the potential welfare impact of the customs union. Finally, factors other than enhanced trade might influence Kenyan policymakers to pursue regional integration, and these include regional cooperation in "behind the border" reforms and the provision of public goods.